The ecological consequences of herbivore-induced plant responses on plant–pollinator interactions. Issue 1 (15th June 2020) - Kessler, André; Chautá, Alexander
Abstract : Plant induced responses to herbivory have long been found to function as plant direct and indirect defenses and to be major drivers of herbivore community and population dynamics. While induced defenses are generally understood as cost-saving strategies that allow plants to allocate valuable resources into defense expression, it recently became clear that, in particular, induced metabolic changes can come with significant ecological costs. In particular, interactions with mutualist pollinators can be significantly compromised by herbivore-induced changes in floral morphology and metabolism. We review recent findings on the evidence for ecological conflict between defending against herbivores and attracting pollinators while using similar modes of information transfer (e.g. visual, olfactory, tactile). Specifically, we discuss plant traits and mechanisms through which plants mediate interactions between antagonists and mutualist and present functional hypotheses for how plants can overcome the resulting conflicts.